2019
DOI: 10.1186/s12944-019-1024-5
|View full text |Cite
|
Sign up to set email alerts
|

The severity of rat liver injury by fructose and high fat depends on the degree of respiratory dysfunction and oxidative stress induced in mitochondria

Abstract: Background High fat or fructose induces non-alcoholic fatty liver disease (NAFLD) accompanied of mitochondrial dysfunction and oxidative stress. Controversy remains about whether fructose or fat is more deleterious for NAFLD development. To get more insights about this issue and to determine if the severity of liver disease induced by fructose or fat is related to degree of mitochondrial dysfunction, we compared the effects of diets containing high fat (HF), fructose (Fr) or high fat plus fructose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 47 publications
4
29
1
Order By: Relevance
“…In addition to its ability to promote de novo lipogenesis and block β-oxidation of fatty acids, fructose consumption seems to cause a drop in ATP and an elevation of uric acid, which can further induce mitochondrial oxidative stress [129]. Moreover, a diet rich in fructose is associated with increased oxidative mtDNA lesions in rat liver coupled with reduced mitochondrial repair capacity [130] and rats consuming a diet high in fat and rich in fructose have increased hepatocyte damage, inflammation, and lipid peroxidation coupled with impaired mitochondrial respiration and activity [131]. Studies show that dietary fructose induces fatty liver [132,133,134] and inflammation in mice after 8–24 weeks of exposure [52,135,136], as well as hepatic fibrosis in rhesus monkeys after seven years [137].…”
Section: Mitochondrial Dysfunction In Non-alcoholic Steatohepatitimentioning
confidence: 99%
“…In addition to its ability to promote de novo lipogenesis and block β-oxidation of fatty acids, fructose consumption seems to cause a drop in ATP and an elevation of uric acid, which can further induce mitochondrial oxidative stress [129]. Moreover, a diet rich in fructose is associated with increased oxidative mtDNA lesions in rat liver coupled with reduced mitochondrial repair capacity [130] and rats consuming a diet high in fat and rich in fructose have increased hepatocyte damage, inflammation, and lipid peroxidation coupled with impaired mitochondrial respiration and activity [131]. Studies show that dietary fructose induces fatty liver [132,133,134] and inflammation in mice after 8–24 weeks of exposure [52,135,136], as well as hepatic fibrosis in rhesus monkeys after seven years [137].…”
Section: Mitochondrial Dysfunction In Non-alcoholic Steatohepatitimentioning
confidence: 99%
“…However, the abolished mt-FAO response in NAFLD can be associated with different mitochondrial alterations, such as reduced oxidative phosphorylation (OXPHOS), diminished ATP production and enhanced sensitivity for mitochondrial permeability transition pore (mPTP) opening [ 12 , 13 , 14 ]. The progression of NAFL towards NASH in a nonreversible manner was reported to involve a prooxidative state and mitochondrial-induced reactive oxygen species (ROS) production, which ultimately alter cellular signaling cascades leading to hepatocellular inflammation and fibrosis [ 15 , 16 , 17 ]. Conversely, recent evidence has questioned the role of oxidative stress as a trigger of NAFL progression.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the oxidative stress response through the progression of the disease represents a challenge to merge features of NAFLD patients and mouse models and provide mechanistic insights and therapeutic opportunities (see Table 4). High-fructose diet [269] Mitochondrial ROS production Lipid peroxidation High-fat and high-fructose diet [270] Superoxide generation Mitochondrial NADPH oxidase 4 (NOX4) High-fat and high-sucrose diet [167] Lipid peroxidation Copper deficient diet [271] Obesity has been widely studied in recent decades, and a close connection between excessive body weight and ROS overproduction has been established [272]. A high-fat low-carbohydrate diet leads to impaired mitochondrial function and increased cellular oxidative damage [273].…”
Section: Dietary Patterns and Oxidative Stress In Nafldmentioning
confidence: 99%
“…A low-fat, fructose-rich diet results in marked oxidative stress levels in hepatocytes [269]. Moreover, García-Berumen et al demonstrated that the supplementation of a HF diet with fructose induces more severe hepatic damage as shown by the inhibition of state 3 and the impairment of Complex I activity, which subsequently promotes further mitochondrial ROS production [270]. Recent work has pointed to the crucial role of fructose and its close relationship with sucrose in the development of NAFLD.…”
Section: Dietary Patterns and Oxidative Stress In Nafldmentioning
confidence: 99%